Membangun Remaja dan Anak-Anak Tang Ceria di HKBP Pakpahan Sitinjak Resort Onan Runggu Distrik VII - Maria Hutahaean, Nelly; Limbong, Sukanto; Deliana Siahaan, Rospita; Raulina, Raulina; Pangaribuan, Yossi (Bulletin of Community Engagement, 2023)
This research has aimed to identify and analyse various efforts and factors involved in fostering cheerful adolescents and children at HKBP Pakpahan Sitinjak, Resort Onan Runggu, District VII. Through a qualitative approach, data were obtained through interviews with church figures, family members, and adolescents themselves. Findings indicate that the development of cheerful adolescents and children in the church is based on a holistic approach that encompasses spiritual, emotional, social, and educational aspects. Factors such as structured religious education, happiness-oriented educational programs, family support, as well as participation in social and church activities are key in creating an environment conducive to positive growth for adolescents and children. The implications of these findings underscore the importance of the church's role as a social development agent in shaping cheerful adolescents and children, and provide guidance for the development of more effective programs in the future. Keywords: Cheerful, Sunday School, Building Youth and Children